Research on Rendering Technology of Ink Painting based on NPR - Sanao Xia (Forest Chemicals Review, 1970)
Chinese ink painting is bred by excellent traditional culture with the integration of water and ink and the alternation of black and white. It began in the Tang and Song Dynasties and still has strong artistic vitality. This paper first describes the application prospect of ink painting rendering technology, then analyzes the research status and development trends at home and abroad, finally focuses on the non photorealistic real-time and implementation method of ink painting style, and tries to put forward a novel ink painting rendering model with great flexibility and expansibility from the essence of ink painting.